The role of local media in identifying the causes of Almaty’s air pollution - Abdikappar, M.; Аlimzhanova, А.; Kaliazhdarova, Sh. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
Climate change poses significant challenges globally, with air pollution emerging as a critical issue, especially in urban areas like Almaty. This study investigates the role of local media, particularly «Almaty Akshamy», in shaping public awareness of air pollution. Through content analysis, the study compares the coverage by «Almaty Akshamy» with other media sources, revealing discrepancies in frequency and depth of reporting. Findings suggest a need for more comprehensive and sustained coverage to address environmental concerns effectively. While «Almaty Akshamy» provides occasional reporting, other sources offer diverse perspectives and insights into air pollution, highlighting the urgency for action. The study emphasizes the importance of collaborative efforts among media, environmental agencies, and government bodies to enhance transparency and promote sustainable practices. By amplifying diverse voices and fostering informed dialogue, media can play a vital role in addressing air pollution and advancing environmental sustainable development of Almaty.